Fracture resistance of endodontically treated mandibular permanent first molars reinforced with diagonal horizontal postdesign: A In vitro study - Karunakaran Jeyaraman Venkataraman; Aravindhan Venkatapathi; Sathyanarayanan Balasubramanian; Chandrika Ramanathan Palanivelu; Senthil Kumar Swaminathan; Leo Sujith Samuel; Sathya Thanapathi (Wolters Kluwer Medknow Publications, 2021)
Aim: This study aims to compare fracture resistance of mandibular first molars reinforced with diagonally placed horizontal posts after endodontic therapy. Materials and Methods: Thirty-two mandibular first molar teeth were selected, standardized, divided into four groups (GP) - GP I (endodontically treated-no post)), GP II (horizontal post-buccolingual), GP III (horizontal postdiagonal), and GP IV (natural teeth). The individual teeth were mounted on bases, coded, and suitably prepared for the facture testing procedure. Results: Buccolingual type of fracture was the most common among the experimental groups with a percentage of incidence of 37.50%. The cuspal type of fracture was the next most common with a percentage of incidence of 25.0%. The incidence of mesiodistal, comminuted, and proximal type of fractures was also observed and had a percentage of incidence of 9.38%, 9.38%, and 9.38%, respectively. Group IV had the highest fracture resistance with a mean value of 1279.82 (N). Group I, Group II, and Group III had mean values of 684.16(N), 756.84(N), and 758.17(N), respectively. There was a statistically significant difference between Gp IV and Gp (I-III) in load values of root fracture (P < 0.05). Conclusion: Within the limitations of this study, it can be concluded that diagonally placed horizontal postdesign has a higher resistance to facture when compared to buccolingually place horizontal postdesign and root canal treated non postgroup. These designs have the potential to be a conservative postendodontic management option. Further evaluation of different horizontal postdesigns and assessment in a clinical setting is recommended.